Flash Flood Risk Perception by the Population of Mindelo, S. Vicente (Cape Verde) - Martins, Bruno Manuel dos Santos de Castro (2019)
São Vicente Island (Republic of Cape Verde) lies within the Sahelian zone and faces several natural hazards, one of which is flash flooding. With the purpose of understanding what factors determine flash flood risk perception, a questionnaire entitled Flash Flood Hazard Perception in Cape Verde was applied to 199 subjects. Analysis of variance (ANOVA) was performed to identify the primary factors associated with the perception of flash flood risk. Di erences between di erent groups under the same impact factor were also compared. The results indicated that certain socio-demographic characteristics of the respondents (gender, level of education, and type of housing) and prior experience correlated with flash flood risk perception. The study also shows statistical di erences between the groups. In general, males and the respondents with a high level of education, homeowners, and people with prior experience have better perception of the flash flood risk. These findings can help decision makers to improve e ective flash flood risk communication policies and flood risk reduction strategies.